Government budgets and poverty reduction in developing countries: a systematic review of the role of social welfare programs and the challenges ahead - Adamu Ahmed, Wudil; Md Saad, Norma; Omercic, Jasmin; Lacheheb, Zakaria; Muhammad, Rislanudeen (European Academy of Sciences Ltd, London, UK., 2023)
This paper presents a systematic literature review of 25 studies published between 2010 and 2021 on the relationship between government budgets and poverty reduction in developing countries. The review identifies a positive relationship between government spending on social welfare programs and poverty reduction. Specifically, increased spending on education and healthcare has been found to have a significant impact on reducing poverty levels. The review also highlights the importance of targeting government spending to specific populations and regions where poverty levels are high, and the challenges and limitations of government spending in poverty reduction efforts, such as corruption and political instability. The paper concludes with important policy implications, such as the need for increased spending on social welfare programs, addressing corruption and mismanagement of government funds, and targeting spending to specific populations and regions where poverty levels are high. The review provides insights for policymakers and practitioners working in the field of poverty reduction, emphasizing the importance of good governance, transparency, and accountability in ensuring that government budgets effectively contribute to poverty reduction.